Development and validation of an instrument to assess student attitudes toward science across grades 5 through 10. Issue 2 (26th July 2017) - Summers, Ryan; Abd‐El‐Khalick, Fouad
Abstract: The aim of the present study is to enable future studies into students' attitudes toward science, and related constructs, by developing and validating an instrument suitable for cross‐sectional designs. Following a thorough review of the literature it was determined that many extant instruments included design aspects that appeared to be limited in some way. The BRAINS (Behaviors, Related Attitudes, and Intentions toward Science) Survey was designed to address core criticisms that have been leveled against many existing instruments. BRAINS was rooted in a theoretical framework drawn from the theories of reasoned action and planned behavior (TRAPB). Initial development involved review by an expert panel, adaptation for online delivery and a pilot on this platform. To establish the psychometric validity of the 59‐item instrument it was administered to a representative, random sample of 1, 291 Illinois students in grades 5 through 10. Confirmatory factor analysis and subsequent refinement yielded a 30‐item instrument with five factors and a good statistical fit including a RMSEA of 0.04 and a CFI of 0.95. The five factors, or constructs, of the final instrument model reflect the underlying TRAPB framework: attitudes toward science, behavioral beliefs about science, intentions to engage in science, normative beliefs, and control beliefs. © 2017 Wiley Periodicals, Inc. J Res Sci Teach 55: 172–205, 2018